Default Risk Analysis In Micro, Small And Medium Enterprises: Does Debt Overhang Theory Occur? - Wahyudi, Imam (Asian Academy of Management (AAM), 2014)
This paper intends to analyse the default risk in micro, small and medium enterprises (MSMEs) and its relation to new debt opportunities, debt overhang theory and growth intention. The results confirm that cash flow, capacity and leverage are the major determinants of firms’ default, while gross margin and efficiency measure are not significant predictors. By analysing the rating transition behaviour, we found that the further the rating migrates, the smaller the probability of transition and that the probability towards default is greater along with the decreased quality rating. By extending the analysis, we found that the debt overhang theory is not applied in relationships between banks and MSMEs.